Profilaxia Antimicrobiana em Cirurgia e a interface com a Comissão de Controle de Infecção - Carneiro, Marcelo; Lima, Amanda Dias; Crestani, Gabriela; Zagonel, Giana; Lena, Virgínia; Krummennauer, Eliane Carlosso; Machado, Janete Aparecida; Rauber, Janine; Lazaroto, Doris Medianeira (Clinical and Biomedical Research, 2011)
carta ao editor não possue resumo